Tabu (Pantang) Saling Berbicara Dalam Masyarakat Batak Karo Desa Lau Penghulu - Basiah Basiah; Nuriza Dora (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The aim of this research is to digitize the "Rebu" taboo of the Karo Batak community on the internet. The steps of the ADDIE theory become a process of digitizing the "Rebu" taboo for the Karo Batak community. analysis, design, development, iv, implementation, and evaluation are some of them. This research uses primary and secondary data sources. Primary data comes from interviews with Karo traditional community leaders, while secondary data comes from books. A web page about the “Rebu” taboo among the Karo Batak people is the output of the research. The website was subjected to expert material and design testers for linguistic testing before digitization. As recommended by experts, the website will be upgraded and digitized at the same time.